Poverty Alleviation Through Potential Zakat Collection: Case of Morocco - Hamida Lahjouji; Monzer Kahf (Jurnal Internasional Ekonomi Islam, 2021)
Morocco, is one of the many countries that still suffer from inequality and a high poverty index despite the economic growth over the last few years. Indeed, This paper aims to demonstrate the effect of Zakat on poverty alleviation and redistribution of wealth by estimating potential Zakat collection in Morocco. The results of this study indicate that potential zakat collection can fill the resources shortfall for the poverty alleviation under 1.9$ and 3.2$ a day. The total of all zakat potential in Morocco are not only sufficient to provide for the shortfall and eliminate the extreme poverty but also can generate surplus.